Le marché de la réassurance en questionnement - Osouf, Serge (Assurances)

(untitled) (HEC Montréal, 1993)
In the speech he delivered at the 3rd Canadian Insurance Congress held in Montreal on May 3rd and 4th, 1993, Mr. Osouf commented on the natural disasters that occurred throughout the world over the past 5 years, particularly in 1992, when insured losses soared to a record of $27.1 billion. Mr. Osouf examines the ever-increasing cost of losses, acute problems such as the deep pocket syndrome in the United States and the underrating of large risks. He mentioned the growing number of insurers and reinsurers who have withdrawn from the market over the past 18 months and the ensuing loss of capacity. According to Mr. Osouf, such a context will give rise to new phenomenons such as tighter underwriting policies, new methods of non-proportional reinsurance, more selective risks acceptance approaches and alternative formulas.